Estudos calorimétricos da adsorção e liberação da pirimetamina e sulfadiazina em matriz de quitosana quimicamente modificada - Lima, Patrícia Soares de (2009)
This work aimed to study the interaction of the drug pyrimethamine (PIR) and sulfadiazine (SDZ) with the biopolymer chitosan chemically modified with glutaraldehyde, after immobilization of copper (Quit-Cu). The release of these drugs in buffer pH 7.0 was also studied by heat-conduction calorimetry at 298 K. The matrices of chitosan modified with glutaraldehyde (QUIT-GLT) were used for immobilization of ions Cu (II), obtaining the material Quit-Cu. This material has 2.347 x 10-5 mol.g-1 of copper. It was obtained values of the interaction energies (Qint) and the amount of PIR and SDZ interacting with Quit-Cu matrix (Nint) at 298 K. Langmuir isotherm described the adsorption equilibrium behaviour in the entire concentration range studied. Negative values found for Gibbs free energy of the PIR and SDZ, ΔG = -16.7 ± 0.4 KJmol-1 and ΔG = - 15.7 ± 0.6 KJmol-1 respectively, confirm the feasibillity of procedures and their spontaneous nature. The release of the drugs from Quit-Cu was also estimated by calorimetry. The data obtained could be described by the model of Power Low. The n values obtained from the fits indicate an anomalous release of PIR and SDZ from Quit-Cu. PIR had a release rate higher than SDZ and a time of release lower than SDZ ( k = 11,31x10-2, 36 min to PIR and K=8,84x10-2, 60 min to SDZ). The results of PIR release were about 40 times greater than the inhibitory concentration dose of the PIR to toxoplasmosis DHFR (0.25 μM), suggesting that the material could be a good carrier to this drug.